Peran Kepala Sekolah Dalam Meningkatkan Profesionalisme Guru - Amalia, Cantika (Universitas Negeri Makassar, 2024)
The main role of the principal as an educational leader in a school is to create a teaching and learning situation so that teachers can teach correctly and students can learn well. Therefore, research was conducted regarding the role of school principals in increasing teacher professionalism at MAN Batu Bara. This type of research is descriptive research using a qualitative approach. The research subjects in this study will involve research subjects, namely the principal and teachers at the school. The results of this research are that the principal carries out his role in accordance with the principal's role as an educator, manager, supervisor, leader, innovator and motivator. The principal understands the characteristics of a leader, the principal also provides opportunities for teachers to continue to develop themselves by involving teachers in various activities, official meetings, KKG, upgrading or training, the principal also always evaluates the teacher's teaching system in the classroom by carrying out activities supervising the class, and the principal always motivates teachers in carrying out their duties as educators.